دراسة جودة مصادر مياه الشرب الجوفية التي تغذي منطقة ( الهنادي – فديو ) وحمايتها من التلوث حالة الدراسة ( آبار الرويمية – نبع ديفة ) - جناد هيثم; ناصر مي (Latakia University Journal -Engineering Sciences Series, 2018)
التلوث مشكلة هامة تعاني منها المجتمعات الحديثة ووجود الملوثات في الموارد المائية وخاصة العذبة يجعل منها مشكلة خطرة ومحددة للنمو والحياة. يهدف البحث إلى تقييم مدى صلاحية مصادر المياه الجوفية للشرب ومقارنتها مع المواصفات القياسية السورية المعتمدة في هذا المجال وكذلك حساب مؤشر الجودة لها ( مؤشر الجودة الكندي ) حيث أجريت تحاليل دورية فيزيائية وكيميائية وبيولوجية لعينات المياه المأخوذة من نقاط الاعتيان المحددة في المنطقة المدروسة على مدار عام كامل بدءا من شهر نيسان2017 وحتى شهر آذار 2018تم خلاله قياس ( الناقلية الكهربائية – العكارة - القساوة الكلية - الأمونيوم– النتريت – النترات- الفوسفات – الكبريتات- الكوليفورم الكلي – الكوليفورم البرازي –الإيشريشيا كولي E-COLi). تبين أن قيم البارامترات الفيزيائية والكيميائية لعينات المياه المأخوذة من نقاط الاعتيان المحددة قد حققت الحدود المسموحة في المواصفة القياسية السورية لمياه الشرب باستثناء بعض قيم القساوة الكلية وشاردة الفوسفات . وجد تلوث جرثومي لعينات المياه في نقاط الاعتيان المحددة على مدار العام حيث تجاوز كل من الكوليفورم الكلي والكوليفورم البرازي والإيشريشيا كولي الحدود المسموح بها في مياه الشرب . كان تصنيف المياه من حيث صلاحيتها للشرب بالنسبة للمصدر المائي الأول ( نبع ديفة ) (وسطا – مقبولا) بينما كان تصنيفها بالنسبة للمصدر المائي الثاني ( آبار الرويمية ) رديئا جدا. Pollution is an important problem experienced by modern societies and the presence of polluants in water resources, especially freshones, makes them a serious and specified problem for growth and life.The purpose of the research is to evaluate the validity of the sources of drinking water and comparison with the Syrian Standards adopted in this field, as well as the calculation of their Quality Index ( Candian Quality Index )where periodic physical ,chemical and biological analysis of water samples taken from the specified sampling points were carried out in the studied area all the year round from April 2017 to March 2018 ,(The Electric Conductivity , Turbidity , Total Hardness , Ammonium , Nitrite , Nitrates , Phosphates ,Sulphates , Total Coliform , Fecal Coliform and E-Coli) were measured . It showed that the values of the physical and chemical parameters of the water samples taken from the specified sampling points achieved the allowed limits of the Syrian Standard for drinking water expect for some values of Total Hardness and Phosphate calcareous.Bacteriological pollution of water samples was found at specific sampling points throughout the year with Total Coliform , Fecal Coliform and E-Coli exceeded allowed limits in drinking water .Th classification of water in terms of drinking capacity for the first water source ( Defa Spring )was acceptable (medium – acceptable ) while its for the second water source ( AL-Rwameya Wells ) was very poor.